2019
DOI: 10.3164/jcbn.18-101
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota disorders cause type 2 diabetes mellitus and homeostatic disturbances in gut-related metabolism in Japanese subjects

Abstract: Few studies have investigated the host microbe metabolic axis in people with type 2 diabetes mellitus (T2DM). This study aimed to determine and compare the nutrient intakes and metabolic markers and to elucidate the relationships among these factors in Japanese T2DM patients and control individuals. Fifty nine Japanese T2DM patients and 59 matched healthy control individuals participated in this study. We examined the differences regarding the participants' dietary habits, microbiota, and fecal short chain fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 38 publications
(52 reference statements)
6
26
1
2
Order By: Relevance
“…Conversely, the abundance of the Bacteroidetes phylum was significantly decreased in patients with HT, HL, T2D, and comorbid conditions. In agreement with our results, Adachi et al demonstrated that T2D patients had larger and smaller fecal populations of Bifidobacterium and Bacteroides , respectively, than the control individuals [ 22 ]. Interestingly, they also demonstrated that T2D patients had consumed more carbohydrates and had lower fecal propionate and butyrate concentrations, and that the levels of Bifidobacterium were negatively correlated with the carbohydrate intake.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the abundance of the Bacteroidetes phylum was significantly decreased in patients with HT, HL, T2D, and comorbid conditions. In agreement with our results, Adachi et al demonstrated that T2D patients had larger and smaller fecal populations of Bifidobacterium and Bacteroides , respectively, than the control individuals [ 22 ]. Interestingly, they also demonstrated that T2D patients had consumed more carbohydrates and had lower fecal propionate and butyrate concentrations, and that the levels of Bifidobacterium were negatively correlated with the carbohydrate intake.…”
Section: Discussionsupporting
confidence: 93%
“…We found no difference in our predictions between Control and Obese groups for propionate metabolism again in contrast to the predictions of Jiao et al [18] but consistent with the predictions of Lee and Ko [30] who found an improvement in metabolic parameters and increased propionate in metformin administered mice on a high fat diet. Our results for predictions on butyrate and propionate are also in accord with a chemical study of human subjects and both of these short chain fatty acids were decreased in faecal material from patients with T2D [31].…”
Section: Discussionsupporting
confidence: 89%
“…Thus, it would be an over simplification to consider the overall level of SCFAs as either good or bad for host metabolic health. There are significant changes in fecal bacterial compositions of T2D vs. healthy individuals [25], with a~30% decrease in fecal contents of propionate and butyrate in T2D subjects [26]. On the other hand, higher fecal concentration of SCFAs is associated with metabolic risk factors including adiposity, waist circumference, and homeostatic model assessment (HOMA) index [27].…”
Section: Scfas Serve As Energy Substrates Especially For Colonocytesmentioning
confidence: 99%